براہوئی ادب اٹ نیاڑی تا شاعری نا روایت : Tradition of Female Poits, in Brahui Literature - Zahida Parveen (Al-Burz, 2019)
Undeniably, Poetry promotes Literacy. It is an individual’s Creativity. Expression of poetry links with physical, intellectual, emotional and natural feelings. Poetry is everywhere, it just needs editing. this article aims to enlighten the works of women in the field of Brahui poetry. there are some women who engraved their names in the history of Brahui poetry. Such as the names of great poetesses are: Tahira Ahsas, Humira Sadaf and Rabiya Khuzdari and many more. Due to these women the Classical and ancient poetry still prevails at the very same way the male writers have also played a great role in the development of Brahui Literature. The rhyme of poetry which was initiated by the ancients and now it is being developed and molded accordingly to the needs and demands of the modern poetry. The art of thyme, melody and logical techniques are also discussed here in. the women who belong to rural areas of Balochistan are presented with their real glamour and shine in this article. which remained unidentified in history of Brahui Literature. No doubt, most of the folk music are sung by women and they made a footstep to progress the literature and Brahui poetry.